Inhibiting DNA methylation as a strategy to enhance adipose-derived stem cells differentiation: Focus on the role of Akt/mTOR and Wnt/β-catenin pathways on adipogenesis - Ceccarelli, S.; Gerini, G.; Megiorni, F.; Pontecorvi, P.; Messina, E.; Camero, S.; Anastasiadou, E.; Romano, E.; Onesti, M. G.; Napoli, C.; Marchese, C. (Frontiers in Cell and Developmental Biology, 2022)
Adipose-derived mesenchymal stem cells (ASCs) represent a valid therapeutic option for clinical application in several diseases, due to their ability to repair damaged tissues and to mitigate the inflammatory/immune response. A better understanding of the underlying mechanisms regulating ASC biology might represent the chance to modulate their in vitro characteristics and differentiation potential for regenerative medicine purposes. Herein, we investigated the effects of the demethylating agent 5-azacytidine (5-aza) on proliferation, clonogenicity, migration, adipogenic differentiation and senescence of ASCs, to identify the molecular pathways involved. Through functional assays, we observed a detrimental effect of 5-aza on ASCs self-renewal capacity and migration, accompanied by actin cytoskeleton reorganization, with decreased stress fibers. Conversely, 5-aza treatment enhanced ASC adipogenic differentiation, as assessed by lipid accumulation and expression of lineage-specific markers. We analyzed the involvement of the Akt/mTOR, MAPK and Wnt/β-catenin pathways in these processes. Our results indicated impairment of Akt and ERK phosphorylation, potentially explaining the reduced cell proliferation and migration. We observed a 5-aza-mediated inhibition of the Wnt signaling pathway, this potentially explaining the pro-adipogenic effect of the drug. Finally, 5-aza treatment significantly induced ASC senescence, through upregulation of the p53/p21 axis. Our data may have important translational implications, by helping in clarifying the potential risks and advantages of using epigenetic treatment to improve ASC characteristics for cell-based clinical approaches.